VPS18 contributes to phagosome membrane integrity in Mycobacterium tuberculosis–infected macrophages - Jani, Charul; Jain, Neha; Marsh, Amanda K.; Uchil, Pooja; Doan, Triet; Hudspith, Meggie; Glover, Owen T.; Baskir, Zach R.; Boucau, Julie; Root, David E.; van der Wel, Nicole N.; Doench, John G.; et al. (Science Advances, 2025)
Mycobacterium tuberculosis (Mtb) has evolved to be exquisitely adapted to survive within host macrophages. The capacity to damage the phagosomal membrane has emerged as central to Mtb virulence. While Mtb factors driving membrane damage have been described, host factors that maintain phagosomal integrity or repair Mtb-induced damage to contain the pathogen remain largely unknown. We used a genome-wide CRISPR screen to identify host factors required to repair Mtb-damaged phagosomal membranes. Vacuolar protein sorting–associated protein 18 (VPS18), a member of the HOPS and CORVET trafficking complexes, was among the top hits. VPS18 colocalized with Mtb in macrophages beginning shortly after infection, and VPS18-knockout macrophages demonstrated increased damage of Mtb-containing phagosomes without impaired autophagy. Mtb grew more robustly in VPS18knockout cells, and the first-line antituberculosis antibiotic pyrazinamide was less effective. Our results identify VPS18 as required for phagosomal membrane integrity in Mtb-infected cells and suggest that modulating phagosome integrity may hold promise for improving the efficacy of antibiotic treatment for TB.
CRIS-Team Scopus Importer:2025-02-17